Effect of pro-inflammatory cytokine priming and storage temperature of the mesenchymal stromal cell (MSC) secretome on equine articular chondrocytes - Jammes, Manon; Contentin, Romain; Audigié, Fabrice; Cassé, Frédéric; Galéra, Philippe (Frontiers in Bioengineering and Biotechnology, 2023)
Context: Osteoarthritis (OA) is an invalidating articular disease characterized by cartilage degradation. In horses, OA is associated with up to 60% of lameness and leads to reduced animal welfare along with extensive economic losses; currently, there are no curative therapies to treat OA. The mesenchymal stromal cell (MSC) secretome exhibits anti-inflammatory properties, making it an attractive candidate for improving the management of OA. In this study, we determined the best storage conditions for conditioned media (CMs) and tested whether priming MSCs with cytokines can enhance the properties of the MSC secretome.Methods: First, properties of CMs collected from bone-marrow MSC cultures and stored at -80°C, -20°C, 4°C, 20°C or 37°C were assessed on 3D cultures of equine articular chondrocytes (eACs).Second, we primed MSCs with IL-1β, TNF-α or IFN-γ, and evaluated the MSC transcript levels of immunomodulatory effectors and growth factors. The primed CMs were also harvested for treatment of eACs, cultured in monolayers or as 3D cultures. Finally, we evaluated the effect of CMs on the proliferation and the phenotype of eACs and the quality of the extracellular matrix of the neosynthesized cartilage. Results: CM storage at -80°C, -20°C and 4°C improved collagen protein accumulation, cell proliferation and the downregulation of inflammation. The three cytokines chosen for the MSC priming influenced MSC immunomodulator gene expression, although each cytokine led to a different pattern of MSC immunomodulation. The cytokine-primed CM had no major effect on eAC proliferation, with IL-1β and TNF-α slightly increasing collagen (types IIB and I) accumulation in eAC 3D cultures (particularly with the CM derived from MSCs primed with IL-1β), and IFN-γ leading to a marked decrease. IL-1β-primed CMs resulted in increased eAC transcript levels of MMP1, MMP13 and HTRA1, whereas IFNγ-primed CMs decreased the levels of HTRA1 and MMP13. Conclusion: Although the three cytokines differentially affected the expression of immunomodulatory molecules, primed CMs induced a distinct effect on eACs according to the cytokine used for MSC priming. Different mechanisms seemed to be triggered by each priming cytokine, highlighting the need for further investigation. Nevertheless, this study demonstrates the potential of MSC-CMs for improving equine OA management.